Analysis of pulsotypes of salmonella typhi isolates and their clinical profiles in typhoid fever patients (Faculty of Medicine Universitas Indonesia, 2003)
A study of genotyping (pulsotyping) of Salmonella typhi (S. typhi) isolates using pulse-field gel electrophoresis (PFGE) methods was performed to examine their genetic diversity, and relationship between genetic characteristics and clinical outcomes. Sixty-six S. typhi isolates obtained from sporadic hospitalized typhoid fever cases were used in this study. Four isolates were found identical and the dendogram constructed showed 33 pulsotypes in which 13 of them can be divided into 30 subtypes. Diversity among them were high as shown by the Dice coefficients that ranged from 0.486 to 1.000. Cluster analysis showed 2 main clusters with 65% degree of similarity, suggested that they were not originated from one clone. Further, at 90% degree of similarity, 9 clusters containing at least 3 isolates were determined to explore any possible existence of relationship between genetic profile and particular clinical outcomes. Clinical manifestations ranged from mild to severe were in fact distributed diversely among these clusters. Although the clinical data obtained were incomplete, 2 out of 4 patients infected by the S. typhi belonged to cluster 1 showed an elevation of total bilirubin, whereas it was not found in 19 other patients distributed in other 8 clusters. Even though specific clinical manifestations were apparently not found to relate with particular clusters of genotypes, S. typhi isolates grouped in cluster 1 seemed to show trophism to hepatobiliary system. (Med J Indones 2003; 12: 13-20) Keywords: S. typhi, typhoid fever, Pulsed-field Gel electrophoresis (PFGE)